2023
DOI: 10.1002/gps.5937
|View full text |Cite
|
Sign up to set email alerts
|

Mortality rates and proximal causes of death in patients with Lewy body dementia versus Alzheimer's disease: A longitudinal study using secondary care mental health records

Abstract: Background Previous studies have shown reduced survival in Lewy body dementia (LBD) compared to Alzheimer’s disease (AD), but the reasons for this are not known. We identified cause of death categories accounting for the reduced survival in LBD. Methods We linked cohorts of patients with dementia with Lewy bodies (DLB), Parkinson’s disease dementia (PDD) and AD, with proximal cause of death data. We examined mortality by dementia group and hazard ratios for each death category by dementia group in males and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Overall, in the case of this study, AD was not underreported in the state of South Carolina as reported in other studies ( Kershenbaum et al, 2023 ). In fact, Alzheimer’s disease was listed as the first immediate cause of death among most racial/ethnic groups who had a diagnosis of dementia.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Overall, in the case of this study, AD was not underreported in the state of South Carolina as reported in other studies ( Kershenbaum et al, 2023 ). In fact, Alzheimer’s disease was listed as the first immediate cause of death among most racial/ethnic groups who had a diagnosis of dementia.…”
Section: Discussionsupporting
confidence: 83%
“…Death certificate information related to AD can be misinterpreted because of other common causes of death, including cardiovascular disease ( Park, 2016 ; Stern et al, 2020 ). Respiratory and nervous system complications ( Kershenbaum et al, 2023 ) are also contributing factors that often supersede AD on death certificates. At the time of the James et al report (2014) AD was estimated as the third immediate cause of death, with dementia having a survival rate like cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%